Serum hyaluronic acid concentrations are increased in cystic fibrosis patients with liver disease. Issue 3 (1st March 2002) - Wyatt, H A; Dhawan, A; Cheeseman, P; Mieli-Vergani, G; Price, J F
Abstract : Aim: To determine whether serum hyaluronic acid (HA) concentrations are abnormal in patients with cystic fibrosis (CF) liver disease, and if so, whether the abnormality is associated with disease severity. Methods: A total of 74 patients with CF were assessed for evidence of liver involvement as indicated by clinical, ultrasound, and biochemical findings. Serum hyaluronic acid concentrations were measured and compared with concentrations in 293 normal controls. Lung function in the CF patients was also recorded. Results: Thirty four CF patients had no evidence of liver disease; in these, serum HA concentrations were similar to those in healthy controls (median (range): 16.1 (9.4–75.1) v 15 (1–77) μg/l). Nineteen CF patients had established liver disease detected by clinical and ultrasound examination, with significantly increased HA concentrations (56.1 (26–355) μg/l). Serum HA concentrations were also significantly increased, although to a lesser extent, in 21 CF patients with an abnormal liver ultrasound scan alone (22.4 (9.5–43.4) μg/l). There was no correlation between serum HA concentration and lung function. Conclusion: Serum HA concentrations were significantly increased in children with clinical or ultrasound evidence of liver disease, being higher in those with more advanced hepatic damage. Despite the inflammation and fibrosis present in CF lungs there was no correlation between HA concentration and lung function, suggesting that high concentrations were a failure of hepatic clearance rather than overproduction in the lung. Longitudinal measurement of HA concentrations may prove a useful marker for the development of significant liver damage in CF patients.